Effect of wall material concentrations on microencapsulation efficiency and oxidative stability of pomegranate seed oil - Damen, Hala Rabea; Mohammed, Nameer Khairullah; Meor Hussin, Anis Shobirin; Muhialdin, Belal J.; Hamad, Muammar Talib; Shrivastava, Arpit (John Wiley and Sons, 2026)
The purpose of this study is to evaluate how different compositions of wall materials affect the efficiency and oxidative stability of pomegranate seed oil (PSO) by spray drying. Three different wall materials (maltodextrin, concentrated milk protein, and lecithin) at three ratios: 1:3 (A), 1:3.5 (B), and 1:4 (C) (oil: wall material) are taken into consideration. All emulsions showed stability over 24 h, with the highest viscosity ratio observed at the 1:4 ratio. The properties of the encapsulated powders were analyzed and the microencapsulation efficiency (MEE) was evaluated at 91.60%, the solubility was 87.66%, the moisture content 2.33 g/100 g, and the bulk density was 0.65 g/cm3. The particle size did not exceed 100 μm. All the particles were spherical, proportionate in size, and free of cracks. A storage stability test, conducted on the encapsulated oil for 28 days with 7 days intervals, showed that the antioxidant content was 69.30% and the peroxide value was 4.00meq/kg compared to free oil, PV was 42.03 meq/kg and DPPH was 55.33%. However, the total phenolic content (TPC) showed a significant decrease in free oil compared to the encapsulated oil with values of 0.57 mg GAE/g and 0.90 mg GAE/g for the encapsulated oil.